Genetic evaluation of F2 and F3 interspecific hybrids of mung bean (Vigna radiata L. Wilczek) using retrotransposon‐based insertion polymorphism and sequence‐related amplified polymorphism markers - Yeni Fatmawati; Ilyas Ilyas; Agus Budi Setiawan; Aziz Purwantoro; Dyah Weny Respatie; Chee How Teo (Indonesian Journal of Biotechnology, 2023)
Mung bean (Vigna radiata L. Wilczek) is a self‐pollinating and indispensable pulse crop in Indonesia. While low yield productivity is a major concern, genetic improvement is possible through interspecific hybridization. However, interspecific hybridization is relatively infrequent and produces low recombination exchanges, significantly limiting crop breeding efficiency. Thus, a comprehensive study is needed of the selection and genetic diversity evaluation of progenies in advanced generations derived from interspecific hybridization using a specific molecular marker. This study aims to confirm the heterozygosity in the F2 population and assess the genetic diversity in F3 mung bean populations resulting from interspecific hybridization between the mung bean and common bean. We designed the retrotransposon‐based insertion polymorphism (RBIP) marker by identifying the syntenic regions in the flanking sequences of retrotransposon insertion in common bean and mung bean. The RBIP marker can be applied to distinguish the heterozygote progenies from the homozygote progenies. Six combinations of sequence‐related amplified polymorphism (SRAP) primers were used in the genotyping of F3 mung bean progenies. The SRAP marker showed a high degree of polymorphism of up to 100%, while high genetic variation was observed within the population (71%) of mung bean progenies. The F3.4 population had the greatest number of genotypes and displayed the highest number of effective alleles, private alleles, and percentage of polymorphic loci, suggesting the existence of high genetic diversity within this population. These genetic diversity data are exceptionally critical for future genetic research since it has potentially high yield production. The genomic and marker‐assisted selection studies will support the major goals of the mung bean breeding program.